Architecture for the mind and body: enhancing wellness in Kimberley - Bester, Darren Elvis (My University, 2014)
For my thesis I have chosen to design an Advanced Fitness Research Center in Kimberley. The primary theme for my project is Motile Phenomenology: A Spatial Exploration of Architecture. My concept for Fitness Research Centre is to explore aspects around space environment and form so as to understand what elements in architecture motivates the users of such spaces. By understanding this dynamic, I will be able to imagine and create certain spaces that serves the differing needs of people using that space. In doing so I would further like to explore how architecture can be possibly designed to get the most out of the experience of each individual. This will help me understand the notion that multi-use spaces should and can be designed to provide a range of experiences created by both the space - “a three-dimensional extension we inhabit” and the designed structure of something - “the form itself” Architectural phenomenology is the way in which individuals reflect emotion over space, and it is through the use of materials and geometries that space can be instinctually constructed in order to impose certain intended reflections upon the users. Space created is not just a combination of forms and materials, but rather for the interface connecting the two. If architecture is created to primarily deal with the surfaces and enclosures it producers with the intention of been occupied by the body, then architects have the ability to design and fabricate technologies which are constructed and realised for the sole purpose of been sensitive to the needs of the users exploring that space. It is through the use of materials and geometries that space can be instinctually constructed in order to impose certain intended reflection upon the users. The architects imagination can somewhat play a very important role in presenting interaction between human body, space created and architecture. Although architecture depends on the materials used for its function and purpose, it is ultimately the relationship between the form and the subject than rather just the performance of the material itself.
Keywords: City planning; Public spaces; Recreation centers designs and plans; South Africa, Kimberley